Examining the role of financial intermediaries in promoting financial literacy and financial inclusion among the poor in developing countries: Lessons from rural Uganda - George Okello Candiya Bongomin; John C. Munene; Pierre Yourougou (Cogent Economics & Finance, 2020)
The main purpose of this study is to establish the mediating role of financial intermediaries in the relationship between financial literacy and financial inclusion of the poor in developing countries with data from rural Uganda. The data for this study were analyzed using Partial Least Square (PLS). The results revealed that financial intermediaries significantly mediates the relationship between financial literacy and financial inclusion. The presence of financial intermediaries such as microfinance banks enhance financial literacy to increase the scope of financial inclusion of the poor in rural Uganda. Thus, policy makers and advocates of financial literacy, especially in developing countries should use financial intermediaries such as microfinance banks to roll out financial literacy programs. This can be achieved through provision of financial literacy clinics, workshops and seminars where the poor can learn about personal finance using hands-on approach. This will help them to make wise financial decisions and choices towards consumption of complex financial products offered by the rural-based financial institutions.
Keywords: 330; microfinance banks; financial literacy programs; financial inclusion; developingcountries; poor households; financial decisions and choices